The effects of cutting speed and feed rate on Bue-Bul formation, cutting forces and surface roughness when machining Aa6351 (T6) alloy - Gokkaya, Hasan (Strojniški vestnik, 2008)
In this paper, the effects of machining parameters such as cutting speed and feed rate on BUE, BUL, main cutting force and surface roughness were experimentally investigated. Optimal and critical cutting parameters were determined. It was found that the cutting speed must be selected above 400-500m/min in order to prevent BUE and BUL formation when machining of AA6351 (T6) alloy with uncoated carbide inserts. The results of this study show that the most important parameter affecting main cutting force and surface roughness is feed rate. As a result of this study, optimum cutting force and optimum feed rate were found in order to minimize surface roughness of the work piece.
Keywords: rezanje; podajanje; zlitine; hrapavost